Carbapenem-resistance and pathogenicity of bovine Acinetobacter indicus-like isolates - Klotz, Peter; Göttig, Stephan; Leidner, Ursula; Semmler, Torsten; Scheufen, Sandra; Ewers, Christa; Justus Liebig University Giessen (My University, 2017)
The objective of this study was to characterize blaOXA-23 harbouring Acinetobacter indicus-like strains from cattle including genomic and phylogenetic analyses, antimicrobial susceptibility testing and evaluation of pathogenicity in vitro and in vivo. Nasal and rectal swabs (n = 45) from cattle in Germany were screened for carbapenem-non-susceptible Acinetobacter spp. Thereby, two carbapenem resistant Acinetobacter spp. from the nasal cavities of two calves could be isolated. MALDI-TOF mass spectrometry and 16S rDNA sequencing identified these isolates as A. indicus-like. A phylogenetic tree based on partial rpoB sequences indicated closest relation of the two bovine isolates to the A. indicus type strain A648T and human clinical A. indicus isolates, while whole genome comparison revealed considerable intraspecies diversity. High mimimum inhibitory concentrations were observed for carbapenems and other antibiotics including fluoroquinolones and gentamicin. Whole genome sequencing and PCR mapping revealed that both isolates harboured blaOXA-23 localized on the chromosome and surrounded by interrupted Tn2008 transposon structures. Since the pathogenic potential of A. indicus is unknown, pathogenicity was assessed employing the Galleria (G.) mellonella infection model and an in vitro cytotoxicity assay using A549 human lung epithelial cells. Pathogenicity in vivo (G. mellonella killing assay) and in vitro (cytotoxicity assay) of the two A. indicus-like isolates was lower compared to A. baumannii ATCC 17978 and similar to A. lwoffii ATCC 15309. The reduced pathogenicity of A. indicus compared to A. baumannii correlated with the absence of important virulence genes encoding like phospholipase C1+C2, acinetobactin outer membrane protein BauA, RND-type efflux system proteins AdeRS and AdeAB or the trimeric autotransporter adhesin Ata. The emergence of carbapenem-resistant A. indicus-like strains from cattle carrying blaOXA-23 on transposable elements and revealing genetic relatedness to isolates from human clinical sources requires further investigations regarding the pathogenic potential, genomic characteristics, zoonotic risk and putative additional sources of this new Acinetobacter species.
Keywords: ddc:630